Regulatory and legal framework for training teachers of physical education and sports in first aid skills in emergency conditions - I.A. Bolotova; N.A. Zadorozhnaya; N.V. Dubkova; I.A. Merkushev; I.A. Bolotova (Theory and Practice of Physical Culture, 2023)
Objective of the study was to substantiate the need to organize training for teachers, trainers and instructors of physical culture and sports in the skills of providing first aid in emergency conditions, taking into account the assessment of the modern regulatory framework. Methods and structure of the study. The analysis of the legislative and regulatory framework in the field of first aid in emergency conditions, as well as literary sources on a given topic, was carried out. Results and conclusions. Consideration of the analysis of the legal framework in the field of first aid in emergency conditions led to the conclusion that the legal documents that form it can form an optimal basis for the development of program and methodological documentation in this area of training for the teaching staff and students of a sports university. The acquired knowledge, skills and abilities to provide first aid in emergency conditions provide an opportunity for specialists working in the field of physical culture and sports to improve their work functions and competencies in their professional career.